Precise phenotyping method using image data for carcass marbling score in Hanwoo cattle. - Wang Yeol Lee; Phuong Thanh N Dinh; Yoonji Chung; Hyo-Jun Lee; Yeong Jun Koh; Hyun Joo Kim; Shil Jin; Jaeho Lee; Jun Heon Lee; Ki Yong Chung; Seung Hwan Lee; Hyung-Yong Kim (PLoS ONE)
With the development of the Korean economy, demand for high-quality beef, specifically Hanwoo beef, is escalating, with marbling traits-measured by the widely used marbling score-being a key contributor to meat palatability. The differences between the high-quality and the lower-quality meat, according to the satisfaction of the customers, are not the result from only the degree of marbling but also from the delicacy of the marbling flecks distribution. Using the computer marbling analysis technique, an index for quantifying marbling fineness of 256 sirloin cuts at 12th- 13th thoracic vertebra named F7 index was developed in this study. F7 index is defined as the standard deviation of the ratios of marbling particles area to the tile area, was developed in this study. At the optimal step size of 70 tiles per axis, F7 index discriminated dramatically the finely marbled and coarsely marbled sirloin with Beef Marbling Score from 6 to 9, with P value = 1.340 × 10-27 < 0.05 of. Although the efficiency of computer image analysis procedure with the F7 index is still being optimized, the F7 index shows great potential to enhance the accuracy of Hanwoo beef quality grading alongside marbling score and support the development of improved breeding strategies for the Hanwoo cattle population in Korea.